Literature and the writer - Meyer, Michael J., 1943- (Rodopi perspectives on modern literature, 2004)
Literature and the Writer was first conceived with the hope the essays would shed light on several dimensions of the authorial craft. It was the hope of the editor that the selected essays would examine not only writers' choice of vocabulary, but also their deliberate selection of grammatical constructions and word order and their seamless weaving together of plots and imagery. Moreover, the analyses would also draw attention to how the writing process impacts the development of characters and the formulation of thematic strands in fiction. Thus, a wide variety of authors are deliberately selected to give the text depth: writers of popular fiction as well as modern classics are included, and contrasts are established between traditional writers and those who prefer to follow experimental trends. Modernists are set against postmodernists, absurdists vs. realists, minority ethnicities vs. majority cultures, and dominant genders appear in contrast to subordinated ones. Clearly, the major tenet of the collection is that the writing profession provides an unending dilemma that deserves to be explored in more detail as readers try to determine how authorial voices confuse while simultaneously elucidating their audience, how texts are constructed by authors and yet deconstructed by the very words they choose to include, how silence functions as inaudible yet audible discourse; and how authorial self-concept shapes not only itself but is also echoed in the fictional characters / writers who appear in the texts.